Pengaruh Profitabilitas, Investment Opportunities Set, Cash Holdings, Kebijakan Hutang, Kebijakan Deviden, Kepemilikan Manajerial, Dan Firm Size Terhadap Nilai Perusahaan(Studi pada Perusahaan Manufaktur yang terdaftar di BEI Periode 2012-2014) - Nurcahaya, Ginanjar, Fauzan, SE, M.Si., Ak (2017)
This research is aimed to determine the effect of Profitability, Investment Opportunities Set, Cash Holdings, Debt Policy, Dividend Policy, Managerial Ownership, and Firm Size on firm value. Independent variables were used Profitability, Investment Opportunities Set, Cash Holdings, Debt Policy, Dividend Policy, Managerial Ownership, and Firm Size. Dependent variable was usedfirm value. The research population was manufacturing companies listed in Indonesia Stock Exchange (IDX) in period of 2012-2014. Sample was collected by purposive sampling method. Total 33 manufacturing companies were taken as study's sample. Analysis method of this research used multiple regression.The results of this research showed thatProfitability,Cash Holdings, Debt Policy, Dividend Policy and Managerial Ownershipdid not significantly effect tofirm value. As forInvestment Opportunities Set and Firm Sizehas significantly effect to firm value. The determination coefficient result showed 96,4%. That's about 96,4% indicated the ability of the independent variables explained the dependent variable while 3,6% explained by the other variables.